IMPROVING PRESERVICE BIOLOGY TEACHERS’ SPATIAL THINKING IN PLANT ANATOMY COURSE THROUGH FRAMING - Ermayanti Ermayanti; Nuryani Y Rustaman; Adi Rahmat (Jurnal Pengajaran MIPA, 2016)
In this study, we reported the implementation of framing in plant anatomy course and how framing improves preservice biology teachers' spatial thinking. Thirty-five preservice biology teachers served as subjects. Spatial thinking were evaluated based on four cognitive processes in spatial thinking: (1) producing representations, (2) maintaining and managing representations in working memory, (3) scanning the representation in working memory, and (4) transforming representations. Results indicated that framing improved preservice biology teachers’ spatial thinking in which all four spatial thinking parameters significantly improved after learning plant anatomy with framing. Framing in a plant anatomy course can improve preservice biology teachers’ spa-tial thinking because questions, guiding sentences, and worked examples aided them in overcoming cognitive stress when engaged in a difficult task.ABSTRAK Dalam studi ini, kami melaporkan implementasi framing dalam mata kuliah anatomi tumbuhan dan bagaimana framing dapat meningkatkan pemikiran spasial calon guru biologi. Tiga puluh lima calon guru biologi menjadi subjek penelitian ini. Keterampilan berpikir spasial dievaluasi berdasarkan empat proses kognitif dalam pemi-kiran spasial: (1) menghasilkan representasi, (2) mempertahankan dan mengelola representasi dalam working memory, (3) memindai representasi dalam working memory, dan (4) mentransformasikan representasi. Hasil penelitian menunjukkan bahwa framing meningkatkan pemikiran spasial calon guru biologi dengan keempat parameter berpikir spasial meningkat secara signifikan setelah pembelajaran anatomi tumbuhan dengan fra-ming. Framing dalam mata kuliah anatomi tumbuhan dapat meningkatkan pemikiran spasial calon guru bio-logi karena pertanyaan-pertanyaan, kalimat-kalimat panduan, serta worked examples membantu mereka dalam mengatasi stres kognitif saat terlibat dalam tugas yang sulit.How to cite: Ermayanti, Rustaman, N.Y., Rahmat, A. (2016). Improving Preservice Biology Teachers’ Spa-tial Thinking in Plant Anatomy Course through Framing. Jurnal Pengajaran MIPA, 21(2), 185-190.